The Probe Team [episode no. 274] - Lazaro, Cheche (Probe Productions, 1993)
A Victory for Justice is an interview of four accused members on Lenny Villa case of an Ateneo de Manila University fraternity. A study conducted on the Metro Manila youth who grew up detatched from their parent is presented in Generation X. Japina is a cultural center stage play portraying the Japanese exploitation from comfort women though the present day Japayuki.